Surgical Approaches to Non-thyrogenic and Non-thymic Mediastinal Tumors of the Thoracic Inlet - Liu, Yu; Lu, Tao; Fan, Hong; Xu, Songtao; Ding, Jianyong; Lin, Zongwu; Wang, Qun (The Thoracic and Cardiovascular Surgeon, 2018)
Background Non-thyrogenic and non-thymic mediastinal tumors of the thoracic inlet are in close proximity to several important vessels and nerves. The narrow confines of the thoracic inlet make complete excision of these tumors difficult, and selecting the appropriate surgical approach is important to successful resection.Methods Records from 57 patients who presented to our department with non-thyrogenic and non-thymogenic tumors of the thoracic inlet from November 2004 to November 2015 were reviewed. All but one of the patients received surgical treatment. Thirty-two tumors were excised via video-assisted thoracic surgery (VATS). Other approaches included thoracotomy, supraclavicular incision, supraclavicular incision plus thoracotomy/VATS, and a posterior midline approach with semi-laminectomy combined with VATS.Results Tumors were resected completely in 54 cases and partially in one. One procedure (VATS) was aborted. There were no surgical mortalities, but there were some postoperative complications. The majority of the tumors were benign neurogenic tumors.Conclusions Most tumors of the thoracic inlet are benign and can be removed via VATS. Thoracotomy is the appropriate approach for large tumors, particularly in cases where the first to second rib cannot be visualized. A supraclavicular approach is recommended for resection of tumors arising from the brachial plexus, and a supraclavicular approach combined with VATS or thoracotomy may be useful for larger masses. A posterior midline approach with semi-laminectomy combined with VATS is appropriate for dumbbell-shaped tumors.
Keywords: non-thyrogenic; non-thymic; thoracic inlet; mediastinal tumors; approach